Determinants of pneumonia among under-five children in Oromia region, Ethiopia: unmatched case-control study - Olana Yadate; Aman Yesuf; Fufa Hunduma; Yitagesu Habtu (BMC, 2023)
Abstract Background Pneumonia is the single largest infectious disease that causes more under-five morbidity and mortality than any other infectious disease in the world, including Ethiopia. The aim of this study is to assess determinants of pneumonia among under-five children in the South West Shewa Zone, Oromia Region, Ethiopia, 2021. Methods We used an unmatched case-control study design from March 15 to April 30, 2021, in the South West Shewa Zone, Ethiopia. A sample of 398 (199 cases and 199 controls) participated in the study. Trained data collectors through a pre-tested structured questionnaire collected data. We used Epi Info to enter data and analyzed using SPSS version 23. We described our data using descriptive statistics. We identified predictors of pneumonia using logistic regression analysis. We declared predictors of pneumonia at a P-value of 0.05 or less. Results Breastfeeding for less than 6 months [AOR:3.51, 95%CI:(1.12,11.00)], lack of Vitamin A supplementation [AOR:3.56,95%CI:(1.58, 8.05)], history of URTI [AOR:9.66, 95%CI:(4.69,19.87)], family child care practices [AOR:6.46, 95%CI, (2.83,14.76)], sleeping with three to five persons in a room [AOR:2.90, 9%CI: (1.23,6.84)], having above five persons in a room [AOR: 3.88, 95%CI: 1.02,14.77), use of wood as a source of fuel [AOR = 3.02 95% CI: 1.41,6.46)] and not opening windows [AOR:2.56 95%CI: (1.21,5.41)] were independent factors of pneumonia among under five children. Conclusion Pneumonia is associated with breastfeeding for less than 6 months, lack of vitamin A supplementation, history of URTI, types of childcare practice, indoor overcrowding, use of wood as a source of fuel, and not opening windows. Therefore, exclusive breastfeeding, improving vitamin A supplementation, early control of respiratory tract infection through promoting good hygiene and ventilation strategies in crowded homes, and promoting how to reduce indoor air pollution through affordable clean stoves will be relevant interventions to reduce under-five pneumonia.